2013
DOI: 10.5012/bkcs.2013.34.8.2531
|View full text |Cite
|
Sign up to set email alerts
|

L-Lactate-mediated Dynamic Kinetic Resolution of α-Bromo Esters for Asymmetric Syntheses of α-Amino Acid Derivatives

Abstract: For asymmetric synthesis of α-substituted carboxylic acid derivatives, a variety of chiral auxiliaries have been used for the dynamic resolution of α-halo esters in nucleophilic substitution. 1 For example, L-lactamide-mediated dynamic kinetic resolution of α-bromo esters was successfully used for the asymmetric preparation of α-aryloxy carboxylic acids and oxazin-2-ones. 2 However, the application of Llactate as a chiral auxiliary was not effective for the dynamic resolution of α-halo esters. 3 In our continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, these methods required air-sensitive catalysts, toxic organic solvents, and several ligands. Few studies have also reported the nucleophilic substitution/cyclization of o -phenylendiamines with α-bromo-α-phenyl ester, α-sulfonyl epoxides or substituted trichloromethylcarbinols ( Scheme 2 ) [ 42 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Recently, the hetero-Diels–Alder reaction of ketene enolates with ortho-benzoquinone diimides [ 68 , 69 ] and a photo-organocatalytic approach have been reported for the synthesis of substituted dihydroquinoxalinones [ 70 ] ( Scheme 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods required air-sensitive catalysts, toxic organic solvents, and several ligands. Few studies have also reported the nucleophilic substitution/cyclization of o -phenylendiamines with α-bromo-α-phenyl ester, α-sulfonyl epoxides or substituted trichloromethylcarbinols ( Scheme 2 ) [ 42 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Recently, the hetero-Diels–Alder reaction of ketene enolates with ortho-benzoquinone diimides [ 68 , 69 ] and a photo-organocatalytic approach have been reported for the synthesis of substituted dihydroquinoxalinones [ 70 ] ( Scheme 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several sequential steps involving protecting groups and specific pre-synthesized starting materials were required. the nucleophilic substitution/cyclization of o-phenylendiamines with α-bromo-α-phenyl ester, α-sulfonyl epoxides or substituted trichloromethylcarbinols (Scheme 2) [42,[64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%